Upper secondary school and pathway selection in the light of educational hierarchies and social stratification: Frjálst skólaval ýtir undir og endurskapar félagslega lagskiptingu - Blöndal, Kristjana Stella; Eiríksdóttir, Elsa; Ragnarsdóttir, Guðrún (Menntavísindasvið Háskóla Íslands, 2024)
Education policy in Iceland emphasises inclusive and comprehensive education for all. Upper secondary schooling is open to all students throughout their lifespan (Jón Torfi Jónasson & Gunnhildur Óskarsdóttir, 2016; mennta- og menningarmálaráðuneyti [Ministry of Education, Science and Culture, MoESC], 2012). However, schools set their own admission policies, and some schools are selective (Elsa Eiríksdóttir, 2022; Elsa Eiríksdóttir et al., 2018). Iceland is currently defined as one school district. Admission governance is based on freedom of choice in a decentralised educational system (Dovemark & Rasmussen, 2022; Elsa Eiríksdóttir et al., 2022). This fact means that upper secondary schools create admission policies based on their ability to compete for students. High-status schools are traditionally those that only offer academic programs preparing students for university, while comprehensive schools that include vocational programmes are considered less prestigious (Ásgerður Bergsdóttir & Berglind Rós Magnúsdóttir, 2018; Kristjana Stella Blöndal et al., 2011; Magnús Þorkelsson, 2011). The hierarchy of upper secondary pathways (academic or vocational) in Iceland clearly reflects the disparity of esteem seen elsewhere (i.e., Billett, 2014; Cedefop, 2014; Elsa Eiríksdóttir et al., 2018). Vocational pathways generally have a lower status than academic pathways that prepare students for university education and are often seen as a landing place for students with lower academic achievement (see Elsa Eiríksdóttir et al., 2018; Nylund et al., 2018). The paper aims to explore how school and pathway selection perpetuate and reflect established hierarchies and social inequalities, especially as it relates to access to upper secondary education for different groups of students and their future prospects. In the study, the 13 upper secondary schools in the Reykjavik metropolitan area were categorised into two school types: Schools that offer only academic programmes and schools that offer both vocational and ...